Holding non-state actors to account for constitutional economic and social rights violations: experiences and lessons from South Africa and Ireland - Nolan, Aoife (Oxford University Press, 2014)
The horizontal application of human rights to non-state actors (NSA) is an evolving and contested legal area both comparatively and at the international level. In light of this, the article discusses mechanisms by which NSA who violate constitutional economic and social rights (ESR) may be held directly accountable by ESR-holders. Its central focus is the horizontal application of constitutional ESR protections to private relationships, where neither party has a state/public function or state nexus. The article reviews developments in two domestic constitutional systems, those of Ireland and South Africa, in order to demonstrate and explain the different approaches that have been adopted to the issue of horizontality by both the constitutional drafters and the courts in those jurisdictions. It employs this comparative analysis to explore many of the key normative objections that have traditionally been raised under liberal constitutional theory in relation to the application of human rights obligations—and those imposed by ESR in particular—to NSA. The article concludes with an evaluation of the effectiveness of the Irish and South African legal models and approaches in terms of holding NSA liable for violations of ESR, outlining key lessons that these national experiences have for the direct horizontal application of ESR at the international level.